Grandfather international : a cross-country comparison of an older people integrated assessment Portugal and Italy - Bivar, Isabel (2016)
Scientists theorize that aging likely results from a combination of many factors. Genes, lifestyle and disease can all affect the rate of ageing. Studies have indicated that people age at different rates and in different ways. Frailty is a state of increased vulnerability with multisystem loss of physiologic reserves and decreased response to stressors, predicting adverse health outcomes. The phenotype of frailty is characterized by: unintentional weight loss, self-reported exhaustion, weakness (low grip strength), slow walking speed and low physical activity. From our knowledge no studies were found that relate the frailty, hearing, the executive functions of language, speech rate and also the swallowing process. The research question is as follows: Is there any relation between frailty speech, language, hearing and swallow? This study is part of a project between Italy and Portugal involving professionals from various fields.